Students’ View on Using Spotify Application to Vocabulary Mastery - Hasanah, Mamluatul; Suryanto, Bradhiansyah Tri (Al Qolam University, 2024)
This research aims to find out the students’ views on using the Spotify application for vocabulary mastery. In this research, the researcher used the qualitative descriptive method. The main instruments used in the data collection were observation and a semi-structured interview. The subjects of this research were eleventh-grade students of MA Al-Husna Dawuhan, Krejengan. The findings of the research reveal that students' positive views and using Spotify regularly can help them with English vocabulary mastery as well as other skills. Thus, it can be concluded that students’ views on using the Spotify application can help them master their vocabulary. Keywords: Spotify Application, Students’ View, Vocabulary Mastery,